STUDY ON CARIES PREVALENCE AND CLINICAL PERFORMANCE OF RESTORATIONS APPLIED ON THE FIRST PERMANENT MOLAR - Mihaela Tănase; Ioana Stanciu; Daciana Zmarandache; Aneta Munteanu; Victor Feraru (Romanian Journal of Stomatology, 2018)
The aim of the study was to evaluate the prevalence of dental caries (Ip), the treatment needs and the clinical performance of restorations applied on the first permanent molar (FPM) in a sample of patients, aged 6 to 10 years, over a period of 36 months. Material and method. A longitudinal descriptive observational retrospective study was performed on a group of 367 patients (184 boys) aged 6-10 years, examined and treated at the Department of Paediatric Dentistry of the Faculty of Dentistry, „Carol Davila” University, Bucharest. It was determined: the number of affected FPM and their diagnosis, the type of treatment applied and the materials used, the time interval until restoration failure occurred and the possible causes of the treatment failure. For the clinical evaluation of the restorations (functional status of the restorations) was used modified RYGE criteria. The longevity of the restorations was evaluated for a period of 30 months. Periodic check-ups were carried out once every 6 months. Statistical data processing was obtained with the SPSS 18.0 program, for p ≤ 0.05. Results. The prevalence of carious lesions of the FPMs was 35.67%, with a higher prevalence for the mandibular molars (SS, p <0.05). 29.88% of patients presented simple caries and 3.79% complicated caries. 91% of the FPMs were filled with glass-ionomer and resin-based composites and 9% with amalgam. The failure rate of the restorations was 22%. The main causes of failure were: the fracture of the restoration and the loss of the marginal adaptation, with the appearance of the secondary caries and tooth discoloration. Conclusions. The prevalence of dental caries on the FPM in the studied age group is high, the carious lesions being detected shortly after their eruption. The rate of successful treatment was 78%. Failure occurred especially in the case of preventive resin restorations and glass-ionomer fillings. Regular dental follow-up is required and the restoration should be chosen taking into consideration the clinical situation (type and depth of the cavity)